KONTRIBUSI MAKANAN JAJANAN TERHADAP TOTAL ENERGI DAN STATUS GIZI PADA ANAK SEKOLAH DI SD INPRES BUKU KECAMATAN BELANG - Vera T. Harikedua; Nonce N. Legi; Masita R. Sarullah (Jurnal GIZIDO, 2015)
Adolescence is a period of growth and maturation process is a fundamental requirement for human life.Growth and physical development are closely related to the nutritional status of children. Consumption offood is one of the main factors deciding the nutritional status of a person. The lack of balance betweenthe intake of nutrients or adequacy will lead to nutritional problems better and more popular among schoolchildren streets habits is very difficult to remove . Penchant school children about foods that are sweet ,sour and savory often exploited by traders or sellers to attract school children .This study aims to determine on Contributions Food Snacks Of Total Energy and Nutritional Status inChildrenElementary School Buku in the District of Belang.This type of research is descriptive analytic cross sectional. Research conducted at the District Belangduring the month of May 2014, with a total sample of 55 people. Types of data collected include theidentity of respondents, nutritional status, street food intake.The results showed that of the 55 samples, there were 47.3% male sex and female sex as much as52.7%. Contributions energy consumption of street food in Buku elementary school- girls that was 9 yearsold as 4 (7.2%) 8-15%, age 10-11 years as many as 26 people (45.5%) 29-42% , contribution energysnack foods are consumed boys in Buku elementary school 9-year-old as many as 5 people (9.1%) 17-21% and 10-11 year age 20 as many as (38.2%) 33 - 47%.Nutritional status of student elementaryschool, 30 (54.4%) had normal nutritional status and obesity 25 people (45.5%).Based on Pearsoncorrelation test, found no association between street food energy contribution to energy intake andnutritional status of Buku elementary school students District of Belang with p = -.166 and -.061 (orgreater than 0.05)